Assessing smart sustainable library practices in higher education: development and validation of instrument - Yunus, Norhazura; Ismail, Mohd Nasir (Institute of Advanced Engineering and Science, 2024)
A smart sustainable library is a new form of a library that blends sustainability and smart libraries with an emphasis on ethics. This study focuses on the need for thorough tools to assess the evolving concept of a smart sustainable library, especially within Malaysian higher education. This study emphasizes the need for a comprehensive tool that combines smart library, sustainability practices, and ethical values in libraries. Developed and conducted a pilot study to validate a new instrument designed to assess these intertwined aspects thoroughly. By distributing a survey to 30 librarians from different academic institutions in Malaysia, we used statistical measures such as Cronbach's alpha, omega, and corrected item-total correlation to assess the validity and reliability of the instrument. The results showed a high level of reliability with Cronbach's alpha at 0.929 and Omega at 0.918, suggesting that the instrument has strong internal consistency and could be effective for wider use. Our research indicates that the newly developed instrument effectively captures the complex nature of smart sustainable libraries, demonstrating its potential for future research and practical use in the field. This research significantly contributes to the library science field by offering a validated tool to evaluate smart sustainable library development.